The Assessment of the Dynamics of Region’s Participation in Interregional and International Exchange Processes Based on the Change in the Ratio of Intermediate and Final Products - Yusupov, Kasim Nazifovich; Yangirov, Azat Vazirovich; Akhunov, Rustem Rinatovich; Toktamysheva, Yuliya Semenovna (Economy of Regions, 2017)
The article presents the hypothesis that the increase in the intermediate consumption caused by the growth of material costs due to innovation and modernization temporarily reduces the level of economic efficiency. This leads to further multiple increases of final product volume, which, in turn, increases the region’s economic potential and competitiveness, provides its enhanced participation in inter-regional and international exchange processes. The authors consider the main factors and conditions that determine the variation of these parameters in the market economy and discuss the intermediate and final product, export, import and others. The results of the analysis, calculations and statistics reveal and confirm the possibility of their measurement with the use of interindustry balances. The study aims at assessing the quantitative interdependence of intermediate and final products growth based on the analysis of interregional and international exchange in the system coordination to macroeconomic indicators of the socio-economic development of the region during the periods of planned and market economy. Another purpose is to determine the directions of the region’s participation in the division of labour and implementation of innovations in order to increase of gross domestic product. On the example of the development of Bashkortostan economy, the authors have revealed that a greater involvement of the region in the foreign economic processes led to the increase in the flow of exports and imports and the simultaneous reduction of production export to other regions of the Russian Federation and import from them. At the same time, the region has focused mainly on the export of fuel and energy products. The proportions of intermediate and final products in the period under review have changed by increasing the final products. That confirms the improvement of conditions for the growth of the region’s competitiveness. On the example of oil-extracting and oil processing industries, the authors have proved that the modernization and introduction of innovative approaches to the organization of production are an effective tool for multiple increases of the final product volume, despite the increase in intermediate products.